English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

1. y = -3x + 4

First: subtract 4 from both sides...

y - 4 = - 3x + 4 - 4
y - 4 = - 3x

Sec: solve for "x" by isolating it on one side > divide everything by - 3...

y/-3 - 4/-3 = - 3x/-3
y/-3 + 4/3 = x
x = y/-3 + 4/3 Or, x = (-1/3)y + 4/3

2. 4x(x + 1) = (2x - 3)(2x + 5)

First: Use distribution > multiply 4x with both terms in the parenthesis and use the foiling method on the right sides...

4x(x) + 4x(1) = 4x^2 + 10x - 6x - 15
4x^2 + 4x = 4x^2 + 4x - 15

Sec: set the equation to "0" > subtract 4x^2 from both sides...

4x^2 + 4x - 4x^2 = 4x^2 - 4x^2 + 4x - 15
4x^2 + 4x - 4x^2 = 4x - 15

*Subtract 4x from both sides...

4x^2 + 4x - 4x^2 - 4x = 4x - 4x - 15
4x^2 + 4x - 4x^2 - 4x = - 15

*Add 15 to both sides...

4x^2 + 4x - 4x^2 - 4x + 15 = - 15 + 15
4x^2 + 4x - 4x^2 - 4x + 15 = 0

Third: combine "like" terms...

15 = 0

*We know 15 doesn't equal 0 > the answer is undefined.

2007-01-14 14:02:04 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

1. not sure if the entire problem is there. With what is showing,
x = -(y - 4)/3

2.
4x(x + 1) = (2x - 3)(2x + 5)
Expanding both sides:
4x^2 + 4x = 4x^2 -6x + 10x - 15
no solution; equation is untrue
4x(x + 1) ≠ (2x - 3)(2x + 5)
15 ≠ 0

2007-01-14 09:35:46 · answer #2 · answered by Helmut 7 · 1 0

Yes I can believe it. This is how one would go about simplifying this equation. 5(-3x-2)-(x-3)= -4(4x+5)+1 (-15x-10)-x+3= (-16x-20)+1 -15x-10-x+3= -16x-20+1 -15x-x+16x= -20-3+1+10 -16x+16x= -23+11 0 =/= -12 Yep, Positive that it is -12 (neg. twelve) . 1) Multiply 5 by everything inside of the parentheses. Move across the (=) sign and multiply -4 by everything in that parentheses. 2) Clear the parentheses 3) That is the equation without () 4) Group like numbers and signs (x's with x's) (numbers w/ #) 5) Simplify SOLUTION 0 is not equal to a -12

2016-05-24 01:46:11 · answer #3 · answered by Anonymous · 0 0

The first one you need to make x the product.

y=-3x + 4

first thing is to get rid of the -3x so + 3x onto both sides.

3x+y = -3x+3x+4

or

3x+y = 4

then minus y off both sides;

3x=4-y

then devide by 3

x=(4-y)/3

2nd one

4x(x+1)=(2x-3)(2x+5)

expand braces;

4x+4=4x+10x-6x-15

add sides;

4x+4=8x-15

minus off 4

4x = 8x -19

minus off 8x

-4x = -19

multiply by -1

4x = 19

x = 4.75

2007-01-14 09:38:39 · answer #4 · answered by Anonymous · 0 1

fedest.com, questions and answers